Leaving Academia: Dual-Career Relationships and Partners’ Attrition from Academic Careers - Jill A. Fisher; Yu Tao; Margaret Waltz; Torin Monahan (Women's Health Reports)
Background: More than one third of academics are coupled with another academic, with more women being in such dual-career relationships. Little is known about how these couples’ experiences affect their attrition from or persistence in academia. Methods: We analyzed survey data of academics at 100 U.S. colleges and universities to answer two research questions: (1) Among all academic partners, who are the most likely to abandon their desired academic careers in terms of their gender, race, and field? (2) What effects does leaving academia have on those partners’ career outcomes? Results: We found that 22% of aspiring academics in academic relationships leave that career pathway. One third leave for personal reasons, including to prioritize their partner’s career. When partners leave academia for personal reasons, they are less likely to be employed in any job and, when employed, are paid less than their counterparts who leave academia for professional reasons. Among our results, we found notable gender differences. Compared with men, women in medicine were more likely to leave academia for personal reasons. Moreover, the earnings of women who leave academia due to personal reasons are the most negatively impacted. Conclusions: These trends indicate that the choices made by dual-career couples in response to the academic job market and to universities’ policies for partner hiring have substantial effects on the demographic makeup of academic research and scholarship. By supporting the needs of academic couples, universities have the opportunity to make their own institutions more diverse and to patch a hole in the leaky pipeline.